Iglulualumiut prehistory : the lost Inuit of Franklin Bay - Morrison, David A. (Mercury series., 1990)
This report compares data from four Thule Inuit sites, including Iglulualuit near the mouth of the Horton River, on the south shores of Amundsen Gulf and on Franklin Bay, Northwest Territories.